Wingless is required for the formation of a subset of muscle founder cells during Drosophila embryogenesis. - Baylies, M.K.; Martinez Arias, A.; Bate, M. (Development, 1995)
The final pattern of the Drosophila larval body wall muscles depends critically on the prior segregation of muscle founder cells. We would like to understand the underlying molecular mechanisms which ensure the precise allocation and placement of these muscle founder cells. We have begun our analysis by examining the role of the segment polarity genes, known to be involved in the patterning of the ectoderm. Mutations in only one member of this class, wingless (wg), lead to the complete loss of a subset of muscle founder cells characterised by the expression of S59. Using the GAL4-targetted expression system, we find that Wingless, a secreted glycoprotein and well characterized signalling molecule, acts directly on the mesoderm to ensure the formation of S59-expressing founder cells. Moreover, we present evidence that Wg can signal across germ layers and that, in the wild-type embryo, Wg from the ectoderm could constitute an inductive signal for the initiation of the development of a subset of somatic muscles.